Modularity in BDI-Based Multi-agent Programming Languages - Dastani, Mehdi; Steunebrink, Bas (Proceedings of the 2009 IEEE/WIC/ACM International Joint Conference on Web Intelligence and Intelligent Agent Technology - Volume 02, 2009)
This paper proposes a module-based vision for designing BDI-based multi-agent programming languages. The introduced concept of modules enables common programming techniques such as encapsulation and information hiding for BDI-based programs, and facilitates the implementation of agent roles and profiles. This vision is applied to a BDI-based agent programming language to which specific programming constructs are added to allow the implementation of modules. The syntax and intuitive semantics of module based programming constructs are explained. An example is presented to illustrate how modules can be used to implement BDI-based multi-agent systems.